Post-Operative 3-Dimensional Contrast-Enhanced Ultrasound (CEUS) Versus Tc99m-DTPA in the Detection of Post-Surgical Perfusion Defects in Kidney Transplants – Preliminary Findings - Stenberg, B.; Chandler, C.; Wyrley-Birch, H.; Elliott, S. T. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: 2800 renal transplants are carried out annually in the UK and it is standard practice to perform a Tc-DTPA renogram examination after surgery to check perfusion. This provides some functional information but suffers from low spatial resolution, is lengthy, immobile and costly and uses ionizing radiation. We surmised that contrast-enhanced ultrasound (CEUS) would provide an accurate alternative with increased speed, resolution (temporal and spatial), cost efficiency and safety.Materials and Methods: 97 renal transplant patients underwent both Tc-DTPA and CEUS after surgery to assess the perfusion of the graft. Tc-DTPA was performed in the nuclear medicine department with at least 10 minutes of continuous screening and a standard dose of 150 mBq Tc-DTPA. CEUS consisted of I. V. 2.4 ml Sonovue contrast agent, 60 seconds continuous capture and a 3 D acquisition of the organ. 3 D CEUS was assessed using QLab analysis software.Results: Tc-DTPA detected 9 perfusion defects of varying size. CEUS detected all these defects plus 14 further defects (0.2 – 17 % of total renal volume) not detected on DTPA. These results demonstrate a statistically significant divergence (p < 0.0001). Retrospective clinical correlation showed ligated polar arteries in 8 of these 14 cases.Conclusion: CEUS will detect perfusion defects seen with Tc-DTPA and due to increased spatial and temporal resolution and multiple scanning angles, will detect further perfusion defects not seen on Tc-DTPA. 3 D CEUS is useful in the quantification of perfusion defects. CEUS is an accurate examination for detecting renal transplant perfusion defects and will detect significantly more defects than DTPA.
Keywords: 3 D ultrasound; radionuclide imaging; transplantation; contrast-enhanced ultrasound